Preparation of Magnesium Hydroxide from Ammonium Chloride by Circulation Method - Li, Yang; Dan, Janming; Li, Hongling (Asian Journal of Chemistry, 2012)
In this paper, the technological conditions for preparation of magnesium hydroxide from ammonium chloride by circulation method are presented. The ammonia gas was prepared via treating carbide residue with ammonium chloride and subsequently passed into the magnesium chloride solution to form the magnesium hydroxide and ammonium chloride. The ammonium chloride was recycled consequently with precipitation separation of the magnesium hydroxide. Key facts on the productivity of magnesium hydroxide were investigated. The best condition is as follows: the molar ratio of ammonium chloride to magnesium chloride is 4.5, the magnesium is 1.5 mol/L, the reaction time is 1 h, the reaction temperature is 25 ºC and the aging time is 2 h. The productivity of magnesium hydroxide can obtain 89.10 % with a purity of above 99.12 % and the cycling rate of ammonium chloride is 69.47 % on this condition. The XRD and SEM were used to characterize the powder products. The results indicate the sheet-shaped magnesium hydroxides with 1 μm diameter were obtained.